Black holes, white holes, and near-horizon physics - Rudeep Gaur; Matt Visser (Journal of High Energy Physics, 2024)
Abstract Black and white holes play remarkably contrasting roles in general relativity versus observational astrophysics. While there is observational evidence for the existence of compact objects that are “cold, dark, and heavy”, which thereby are natural candidates for black holes, the theoretically viable time-reversed variants — the “white holes” — have nowhere near the same level of observational support. Herein we shall explore the theoretical possibility that the connection between black and white holes is much more intimate than commonly appreciated. We shall first construct “horizon penetrating” coordinate systems that differ from the standard curvature coordinates only in a small near-horizon region, thereby emphasizing that ultimately the distinction between black and white horizons depends only on near-horizon physics. We shall then construct an explicit model for a “black-to-white transition” where all of the nontrivial physics is confined to a compact region of spacetime — a finite-duration finite-thickness, (in principle arbitrarily small), region straddling the naïve horizon. Moreover we shall show that it is possible to arrange the “black-to-white transition” to have zero action — so that it will not be subject to destructive interference in the Feynman path integral. This then raises the very intriguing possibility that astrophysical black holes might be interpretable in terms of a quantum superposition of black and white horizons — a “gray” horizon.